Leaf carbohydrates influence transcriptional and post-transcriptional regulation of nocturnal carboxylation and starch degradation in the facultative CAM plant, Mesembryanthemum crystallinum - Taybi, Tahar (Journal of plant physiology, 2017)
Copyright © 2017 Elsevier GmbH. All rights reserved.